Lifestyle Behaviors and Quality of Life Among Older Adults After the First Wave of the COVID-19 Pandemic in Hubei China - Duan, Yanping; Peiris, D. L. I. H. K.; Yang, Min; Liang, Wei; Baker, Julien Steven; Hu, Chun; Shang, Borui (Frontiers in Public Health, 2021)
Background: Older adult quality of life (QoL) is facing huge challenges during the COVID-19 pandemic. New normal lifestyle behaviors, including getting adequate physical activity (PA), consuming sufficient fruits and vegetables (FV) and enacting individual preventive behaviors (frequent hand washing, facemask wearing, and social distancing), as a significant determinant for QoL, have not been adequately addressed in older adults during the pandemic. This study aimed to investigate the characteristics of QoL in Chinese older adults after the first wave of the COVID-19 pandemic in Hubei China. The objective of the study was to examine any associations of lifestyle behaviors with QoL, and to identify the moderating role of socioeconomic indicators in the associations identified. Methods: A cross-sectional study was conducted in Hubei, China, from June 15, 2020, to July 10, 2020. Five hundred sixteen older adults completed an online survey (mean age = 67.6 ± 6.6; 57.9% women). The questionnaire consisted of demographic information, covariates (chronic diseases and infected cases of acquaintances), lifestyle behaviors [PA stage, FV intake (FVI) stage and three preventive behaviors], and QoL. T-tests, ANOVA tests, multiple linear regression models with simple slope analyses were used to test the hypotheses. Results: QoL significantly differed in relation to economic situation, chronic diseases, marital status, education, living situation, age group, and professional status. Participants' economic situation (βaverage vs. below average = 0.17, p < 0.01; βabove average vs. below average = 0.15, p < 0.01), chronic diseases (βyes vs. no = 0.19, p < 0.001), FVI stage (β = 0.21, p < 0.001), and preventive behaviors (β = 0.10, p < 0.05) indicated a significant association with QoL. Education level and economic situation significantly interacted with preventive behaviors on QoL, respectively (βpreventive behaviors × educational level = −1.3, p < 0.01; βpreventive behaviors × economic situation = −0.97, p < 0.05). Conclusions: Findings emphasize the importance of enhancing FVI and preventive behaviors on QoL improvement in older adults during the COVID-19 pandemic. Older adults who are in a lower economic situation with lower education levels should be given priority when implementing interventions to improve preventive behaviors and QoL in older adults.